Kebijakan Penanganan Pembiayaan Bermasalah pada Bank Syariah dan Konvensional Perspektif Ekonomi Syariah Pasca Bencana di Sulawesi Tengah - Syaakir Sofyan (Prodi Perbankan Syariah FAI UMT, 2020)
The natural disaster that occurred in Palu on September 28, 2018 was an earthquake that occurred due to the Palu Koro fault activity, which had a magnitude of 7.4 on the Richter scale, which had an impact on bank performance, primarily related to non-performing loans (NPLs). The purpose of this study was to determine the policy of handling non-performing loans for disaster victims as well as an analysis of the Islamic economy of the policy. This research belongs to the category of qualitative research with a descriptive analysis approach. The object under study is Islamic and conventional banks. The handling of problem loans still has several things that need to be clarified, especially for write offs and write offs that are not regulated in OJK Regulation No. 45/POJK.03/2017 concerning Special Treatment of Credit or Financing for Certain Areas in Indonesia Affected by Natural Disasters. In addition, the determination of credit quality and restructuring with a period of 3 years in special treatment for areas affected by natural disasters is too early to be determined, because the impact of natural disasters for each customer is different and allows some customers to make bad intentions by utilizing the situation to avoid payment.